2011
DOI: 10.1177/1098300711412601
|View full text |Cite
|
Sign up to set email alerts
|

Illinois Statewide Positive Behavioral Interventions and Supports

Abstract: More than 1,000 Illinois schools are implementing schoolwide positive behavior support (SWPBS) to enhance outcomes for students and staff. Consequently, Illinois established layered support structures to facilitate scaling up SWPBS. This paper describes the development of this infrastructure and presents the results of HLM analyses exploring the effects of implementing SWPBS, with and without fidelity across time, on student behavior and academic outcomes (office discipline referrals, suspensions, and state-wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
97
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(104 citation statements)
references
References 16 publications
6
97
1
Order By: Relevance
“…Studies that focused on specific interventions implemented as part of SWPBIS implementation (e.g., Benner, Nelson, Sanders, & Ralston, ; Wills, Kamps, Abbott, Bannister, & Kaufman, ) or those that focused exclusively on teacher outcomes (e.g., teacher self‐efficacy) were removed (e.g., Ross, Romer, & Horner, ). Also, studies with control groups that also received SWPBIS training (e.g., Simonsen et al, ; Vincent, Randall, Cartledge, Tobin, & Swain‐Bradway, ) were excluded. Two studies that examined the same outcomes with the same sample but at different periods, one with a 3‐year trial (Bradshaw, Koth, Bevans, Ialongo, & Leaf, ) and one with a 5‐year trial (Bradshaw, Koth, Thornton, & Leaf, ).…”
Section: Methodsmentioning
confidence: 99%
“…Studies that focused on specific interventions implemented as part of SWPBIS implementation (e.g., Benner, Nelson, Sanders, & Ralston, ; Wills, Kamps, Abbott, Bannister, & Kaufman, ) or those that focused exclusively on teacher outcomes (e.g., teacher self‐efficacy) were removed (e.g., Ross, Romer, & Horner, ). Also, studies with control groups that also received SWPBIS training (e.g., Simonsen et al, ; Vincent, Randall, Cartledge, Tobin, & Swain‐Bradway, ) were excluded. Two studies that examined the same outcomes with the same sample but at different periods, one with a 3‐year trial (Bradshaw, Koth, Bevans, Ialongo, & Leaf, ) and one with a 5‐year trial (Bradshaw, Koth, Thornton, & Leaf, ).…”
Section: Methodsmentioning
confidence: 99%
“…This warrants an analysis of whether there are, in fact, particular critical features that are necessary or sufficient to produce changes in student outcomes (OSS, in-school suspension [ISS], and ODR). Simonsen et al (2012) attempted to address the relationship between fidelity of implementation and student outcomes by analyzing historical school-level data from Illinois. The authors modeled longitudinal differences in the number of ODR, ISS, and OSS by fidelity status, defined as a SET score of 80 or above.…”
Section: Research-article2015mentioning
confidence: 99%
“…However, some of these studies did not comprehensively consider implementation fidelity, which refers to the degree to which the core features of SWPBIS are implemented exactly as they are designed and intended. This is problematic considering the research that has found positive associations between implementation fidelity and positive academic and behavioral student outcomes (Marin & Filce, ; Pas & Bradshaw, ; Simonsen et al, ). Some of the studies that did not find a significantly positive relationship between SWPBIS and academic achievement either did not consistently measure implementation fidelity (e.g., Caldarella et al, ) or categorized or dichotomized implementation fidelity variables (e.g., Freeman et al, ; Gage, Sugai, Lewis, & Brzozowy, ; Noltemeyer et al, ), which limits the variability within these fidelity measures and also makes it more difficult to detect small changes in implementation.…”
Section: Outcomes Associated With Pbismentioning
confidence: 99%